To determine the correct recursive equation for the arithmetic sequence 6, 2, -2, -6, ..., we first identify the pattern of the sequence.
The first term \( a_1 = 6 \).
To find the common difference, we can subtract the second term from the first term:
\[ a_2 - a_1 = 2 - 6 = -4 \]
Similarly:
\[ a_3 - a_2 = -2 - 2 = -4 \]
\[ a_4 - a_3 = -6 - (-2) = -4 \]
The common difference is \(-4\).
Now, using the common difference, we can write the recursive formula. The first term is:
\[ a_1 = 6 \]
And each subsequent term is found by subtracting 4 from the previous term:
\[ a_n = a_{n-1} - 4 \]
Thus, the correct recursive equation is:
Option #2: \( a_1 = 6\), \( a_n = a_{n-1} - 4 \).